Predicting inflation in Euroland: the Pstar approach - Joachim Scheide; Mathias Trabandt (Kiel Institute of World Economics (IfW), 2000)
Inflation is a monetary phenomenon. While this statement is widely accepted in terms of a long-run relationship, the quantity theory has been made operational also for the short-run dynamics of inflation by so-called Pstar models. An error correction model with quarterly data for the Euro Area is estimated to test whether the price gap has an impact on consumer price inflation. The response of the HICP is strongly positive. Other factors such as raw material prices and unit labor costs also have some explanatory power. The model is used for shock analysis and out-of-sample forecasts. All in all, the Pstar model can be a useful tool for predicting inflation also in Euroland.
Keywords: E31; C53; C22; 330; forecasting; error correction models; inflation process; Inflation; Prognoseverfahren; Quantitätstheorie; P-Star; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten